2016
DOI: 10.1039/c5ra20151a
|View full text |Cite
|
Sign up to set email alerts
|

A new functionalized magnetic nanocomposite of poly(methylacrylate) for the efficient removal of anionic dyes from aqueous media

Abstract: A magnetic nano-adsorbent was synthesized via the radical polymerization of methyl acrylate on modified Fe3O4 MNPs, followed by amidation of the methyl ester groups using pentaethylenehexamine, to create active sites for adsorption of anionic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Magnetite nanoparticle (MNP) has attracted great attention in recent years in biomedical and biotechnological applications [1][2][3][4][5] owing to its magnetically guidable properties [2], high surface area-to-volume ratio [4], high saturation magnetization [6,7], low toxicity, and high biocompatibility [8]. These intriguing properties make MNP as an ideal candidate for use in various biomedical fields such as drug delivery [5], diagnostics, therapeutics [2,9,10], and magnetic separation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetite nanoparticle (MNP) has attracted great attention in recent years in biomedical and biotechnological applications [1][2][3][4][5] owing to its magnetically guidable properties [2], high surface area-to-volume ratio [4], high saturation magnetization [6,7], low toxicity, and high biocompatibility [8]. These intriguing properties make MNP as an ideal candidate for use in various biomedical fields such as drug delivery [5], diagnostics, therapeutics [2,9,10], and magnetic separation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…When individual unique properties of both MNP and polymer matrix were combined, multifunctional nanocomposite serving as a platform for further conjugation with desirable bioentities can be obtained [16,17]. Thus, this hybrid nanocomposite has been particularly used in the biological field such as drug delivery system [18,19], controlled release [16,20,21], and magnetic separation [11][12][13]. Previous works have reported the synthesis of MNP-polymer nanocomposite having both good magnetic separation ability and good water dispersibility for drug controlled release [4,16] and for conjugation with bioentities [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selective adsorption can be greatly improved for the enrichment of pollutants due to introduction of large numbers of active sites. Pourjavadi et al reported a new functionalized magnetic nanocomposite of poly(methylacrylate) for the efficient removal of anionic dyes from aqueous media [ 27 ]. Polycatechol, resulting from the polymerization of catechol catalyzed by Fe(III) [ 28 30 ], has been exploited in surface modifications as adhesives and coatings over a wide range of both organic and inorganic materials due to their unique thermal, structural properties, and the ability to form stable complexes with metal oxides [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Therefore, purication of industrial effluents containing even traces of dyes is necessary before discharging into the environment. 13 In this vein, recently, several methods such as biological treatment, 14 chemical oxidation, 15 photocatalytic degradation, 16 membrane ltration 17,18 and adsorption [19][20][21][22][23][24][25] have been developed for dye removal from wastewater aiming to decrease their impact on the environment. Among the above-mentioned methods, adsorption is considered as a simple, effective and economic method due to its high efficiency, high diversity in design, and ability to separate a wide range of pollutants from industrial effluents.…”
Section: Introductionmentioning
confidence: 99%